2013
DOI: 10.1111/jog.12111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of poor embryo development in postovulatory aged oocytes: Mini review

Abstract: Oocyte quality is a key factor in determining embryo development; however, we have a poor understanding of what constitutes oocyte quality or the mechanisms governing it. Postovulatory aging of oocytes that have not been fertilized for a prolonged time after ovulation is known to significantly impair oocyte quality and subsequent embryo development after fertilization. Embryos derived from postovulatory-aged oocytes are prone to undergo apoptosis due to the decreased Bcl-2 expression. Postovulatory aging of oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 61 publications
(166 reference statements)
2
56
0
10
Order By: Relevance
“…Most authors suggest that an increase in reactive oxygen species (ROS) is involved in postovulatory oocyte ageing (Figure 2). ROS are chemically reactive molecules containing oxygen, such as oxygen ions and peroxides, which may act as an initiator for over-ripening in human Takahashi et al, 2013) and mouse oocytes . Therefore, an increase in the ROS levels of the oocyte could be associated with the progress of ageing (Takahashi et al, 2003;Tatone et al, 2011).…”
Section: Egg Cellular and Molecular Changes Through Oocyte Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors suggest that an increase in reactive oxygen species (ROS) is involved in postovulatory oocyte ageing (Figure 2). ROS are chemically reactive molecules containing oxygen, such as oxygen ions and peroxides, which may act as an initiator for over-ripening in human Takahashi et al, 2013) and mouse oocytes . Therefore, an increase in the ROS levels of the oocyte could be associated with the progress of ageing (Takahashi et al, 2003;Tatone et al, 2011).…”
Section: Egg Cellular and Molecular Changes Through Oocyte Ageingmentioning
confidence: 99%
“…This can have consequences for different Figure 2. Schematic of the mechanism of poor embryo development in post-ovulatory oocyte ageing (obtained from Takahashi et al, 2013).…”
Section: Egg Cellular and Molecular Changes Through Oocyte Ageingmentioning
confidence: 99%
“…Increased plasma and FF oxidative stress markers and decreased levels of antioxidants have been already related to poor in vitro fertilization (IVF) outcome [39][40][41]. Indeed, several studies reported the relationship between follicular development, poor oocyte quality and fertilization, embryonic development, and decreased female fertility and oxidative stress, both at systemic and local level.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, aged oocytes have lowering CSF levels due to gradual decay, destabilizing MPF, leading to an increase in spontaneous activation by physicochemical environmental events (Wakayama et al, 2003). However, despite being easier to activate, aged oocytes have lower potential for further embryo development (Chian et al, 1992;Takahashi, 2013).…”
Section: Universal Cytoplastmentioning
confidence: 99%